A Pragmatic Analysis of Flouting Maxim Performed by The Main Characters of Radium Girls Movie - Alvionena Safitri, Elysa Hartati (Pusdikra-Publishing.com, 2023)
A movie becomes a big source for both entertainment or education. Radium Girls is a play written by D. W. Gregory, to be filmed and released in 2018. It is an interesting movie because the story is based on a historical true story that happened in the 1920s. Radium Girls is analyzed by exploring the flouting maxim which appears in the dialogues between the characters of the play and to find out the implicit meaning of the flouting maxim. To find out the flouting maxim uttered by main characters (the girls) in this Radium Girls movie based on the stages found in a narrative circle in this study, the researcher used a descriptive qualitative method. There are 71 utterances employed by the main characters of the Radium Girls movie. They were distributed in flouting maxim of quality; three data, flouting maxim of quantity; thirty-five data, flouting maxim of relation; twenty-one data, and flouting maxim of manner; twelve data. The speech act is used to describe what utterances are intended to do. Declaratory can be used to flout maxim of quantity and maxim of manner. Expressive speech act can be used to flout maxim of quality, maxim of quantity, maxim of relation, and maxim of manner. Assertive can be used to flout all type of maxim while commissive can be used to flout maxim of quantity and maxim of relation. The last, directory can be used to flout maxim of quantity and maxim of relation.